Vestibular neuritis in pediatrics: a mini review - Farahmandi, Fargol; Nikkhah, Ali; Khalilian, Mohammad Reza; Parhizgar, Parynaz (Student Research in Translational Medicine, 2022)
Background and aims: Vestibular neuritis (VN) is a clinical feature, portrayed by acute and prolonged vertigo from peripheral source without associated auditory symptoms. the appearance of vestibular disease may also lead to cognitive deficits, including attention deficits. Therefore, the purpose of this mini-review is to describe the clinical characteristics, etiology, prevalence and treatment of vestibular neuritis in children. Materials and methods: The present study was conducted in January 2021. The study was performed based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) checklist. The comprehensive search was conducted in the literature of the international databases (PubMed, Scopus, and Google Scholar) and national databases including scientific information database (SID), Magiran and iranDoc until January 13, 2021. Search keywords included "vestibular neuritis", "vestibular disorder", "balance disorder", and "pediatrics" or "children" or "adolescent" or "infants". The time limit for publishing articles was from 2010 onwards. Results: In the initial search, 17 articles were extracted. After reviewing the title and abstract, 6 studies were excluded. In the evaluation and full-text review, 2 articles were excluded due to low quality and lack of access to the full text of another article. Finally, 9 studies were included in the present study. Conclusion: We conclude that vestibular neuritis should always be considered in pediatric patients presenting with vertigo, and especially with nasopharyngeal viral infection, in addition to other differential diagnoses. Vestibular neuritis is one of the most common diseases in vestibular disorders in children, and different prevalence rates have been reported in studies so it needs further investigation. Once the diagnosis of vestibular neuritis is confirmed, symptomatic treatment should be started for the child.